Refugee women's experience of the resettlement process: a qualitative study - Elisabeth Mangrio; Slobodan Zdravkovic; Elisabeth Carlson (BMC, 2019)
Abstract Background Resettlement can be particularly challenging for women as having a lower socioeconomic status and language barriers, may impede women's access to education, employment opportunities, health-care services, as well as the cultural, social, material and resilience factors that facilitate adjustment and adaption. Thus, the aim of this study is to further explore the perception of refugee women in Sweden concerning their situation during active participation in the resettlement process in the country. Methods Qualitative interview study with 11 recently arrived refugee women who had received their residence permits and were enrolled in the resettlement process. The interviews were conducted in Swedish with the support of an authorized Arabic translator present by telephone. Results Refugee women suffered from being separated from their loved ones and felt compelled to achieve something of value in the host country. All experienced both physical and mental anguish. Conclusions Stakeholders in societies that receive refugee women should stress the importance of finding opportunities for and fast entrance into employment in the host countries. This would be beneficial for the integration and well-being of refugee women after migration.